Elevated C-reactive Protein Levels Independently Predict the Development of Prediabetes Markers in Subjects with Normal Glucose Regulation - Kato, Katsuhito; Otsuka, Toshiaki; Saiki, Yoshiyuki; Kobayashi, Nobuyuki; Nakamura, Takayuki; Kon, Yoichi; Kawada, Tomoyuki (Experimental and Clinical Endocrinology & Diabetes, 2019)
Aims Prediabetes is a precursor of diabetes and increases the risk of cardiovascular disease. Individuals with prediabetes reportedly have higher C-reactive protein levels, which is a risk factor for diabetes, relative to individuals with normal glucose regulation. Inflammation may play a role in the very early-phase deterioration of glucose metabolism, although there is insufficient knowledge regarding this relationship. Thus, we examined the association between serum C-reactive protein level and the development of three prediabetes markers.Methods This study included 743 subjects with normal glucose regulation at baseline who completed oral glucose tolerance tests at baseline and after approximately 5 years. Subjects with a history of cardiovascular disease were excluded.Results During the 5-year follow-up, 55 subjects developed isolated impaired glucose tolerance (IGT; 2h-plasma glucose levels of 7.8–11.0 mmol/L), 24 subjects developed isolated impaired fasting glucose (IFG; fasting plasma glucose levels of 6.1–7.0 mmol/L), 3 subjects developed IFG plus IGT, and 53 subjects developed isolated elevated glycated hemoglobin levels (HbA1c; level of 41–47 mmol/mol). The multivariate analysis revealed that, relative to the lowest quartile, the highest serum C-reactive protein quartile was independently associated with an increased risk of developing isolated elevated HbA1c levels (odds ratio: 2.95, 95% confidence interval: 1.16–7.51, P=0.024) and marginally associated with an increased risk of developing impaired glucose tolerance plus diabetes. However, C-reactive protein levels were not associated with an increased risk of developing IFG.Conclusions Elevated serum C-reactive protein levels independently predicted elevated HbA1c levels, but not IFG.
Keywords: inflammation; impaired glucose tolerance; impaired fasting glucose